Reagent Controlled Glycosylations for the Assembly of Well-Defined Pel Oligosaccharides - Wang, Liming (J Org Chem, 2020)
[Image: see text] A new additive, methyl(phenyl)formamide (MPF), is introduced for the glycosylation of 2-azido-2-deoxyglucose building blocks. A linear α-(1,4)-glucosamine tetrasaccharide was assembled to prove the utility of MPF. Next, a hexasaccharide fragment of the Pseudomonas aeruginosa exopolysaccharide Pel was assembled using a [2 + 2 + 2] strategy modulated by MPF. The used [galactosazide-α-(1,4)-glucosazide] disaccharide building blocks were synthesized using a 4,6-O-DTBS protected galactosyl azide donor.